Administration of bone marrow stromal cells in sepsis attenuates sepsis-related coagulopathy. (18th May 2016) - Tan, Lifei; Huang, Yueyue; Pan, Xiaojun; Quan, Shichao; Xu, Shunyao; Li, Dequan; Song, Lijun; Zhang, Xiaomin; Chen, Wanzhou; Pan, Jingye
Abstract: Introduction Coagulopathy plays an important role in sepsis. The aim of this study was to determine whether bone marrow stromal cell (BMSC) administration could attenuate coagulopathy in sepsis. Materials and methods In vitro : endothelial cells were cultured with/without BMSCs for 6 h following LPS stimulation and were collected for thrombomodulin (TM) and endothelial protein C receptor (EPCR) measurements. In vivo : Thirty-six mice were randomized into sham, sepsis, and sepsis + BMSC groups (n = 12 each group). Sepsis was induced through cecal ligation and puncture (CLP). BMSC infusion was started at 6 h after CLP. Lung tissues and plasma samples were collected at 24 h after CLP for enzyme-linked immunosorbent assay (ELISA), quantitative real-time RT-PCR, western blot, and immunohistochemistry analysis. Results In vitro : BMSCs attenuated the decrease in TM and EPCR mRNA and protein expression levels in LPS-stimulated endothelial cells. In vivo : BMSC treatment decreased lung injury and mesenteric perfusion impairment, and ameliorated coagulopathy, as suggested by the reduction in elevated TF, vWF, and TAT circulation levels. BMSC infusion decreased TF mRNA transcription and protein expression levels in lung tissues, and increased TM and EPCR mRNA transcription and expression levels. Discussion BMSC administration attenuated coagulopathy, and decreased lung injury and mesenteric perfusion impairment in sepsis. Key messages: BMSCs increased the expression of TM and EPCR from endothelium cells exposed to LPS in vitro . BMSC treatment attenuated lung injury and coagulopathy in the mice cecal ligation and puncture (CLP) model. BMSC administration-attenuated coagulopathy is related to the reduced expression of TF and increased expression of TM and EPCR.